1980
DOI: 10.7326/0003-4819-93-1-62
|View full text |Cite
|
Sign up to set email alerts
|

Drug Therapy in Renal Failure: Dosing Guidelines for Adults

Abstract: Data are presented in tabular form that provide guidelines for drug use in adult patients with renal insufficiency. The data are derived from the current medical literature. If specific information about a drug is unavailable or conflicting, emphasis is given to normal pharmacokinetic variables in arriving at recommendations for therapy. Nephrotoxicity or adverse effects in patients with renal disease are noted and adjustments for dialysis suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(18 citation statements)
references
References 349 publications
0
18
0
Order By: Relevance
“…Amphotericin B is a large molecule and is in part eliminated by excretion into bile (10). Impaired elimination in patients with renal failure has not been observed (17), and dosage modifications in patients with renal failure are not advocated (4,16). It was therefore surprising to find that levels of amphotericin B in tissues were different between salt-depleted and salt-loaded rats in both the kidney and the liver, despite no evidence of accumulation in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B is a large molecule and is in part eliminated by excretion into bile (10). Impaired elimination in patients with renal failure has not been observed (17), and dosage modifications in patients with renal failure are not advocated (4,16). It was therefore surprising to find that levels of amphotericin B in tissues were different between salt-depleted and salt-loaded rats in both the kidney and the liver, despite no evidence of accumulation in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, when amino glycoside dosages are increased above recommended doses in an attempt to assure optimal efficacy, can an increased risk of toxicity be excluded? The recommendation that patients with shorter drug half-lives receive larger doses at more frequent intervals cannot be supported by existing literature [12], although patients with longer drug half-lives that require less drug less frequently have been the major focus of clinical pharmacokinetics [21][22][23]. To further confuse the issue, observations in experimental animals have shown that intermittent administration of aminoglycoside doses results in less nephrotoxicity than continuous infusion of the same total dose, despite the fact that tissue levels were identical [24,25],…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the elderly subjects may experience more side effects after administra tion of the recommended dosage of sulfisoxa zole for young adults. On the basis of our findings, the elderly subjects may benefit from a dosage adjustment of sulfisoxazole similar to that recommended in the therapy of patients with renal insufficiency [2].…”
Section: Discussionmentioning
confidence: 99%
“…Side effects of sulfisoxazole such as crystalluria [2] and gastrointestinal discom fort [11] are related to higher plasma levels of the drug. Therefore, the elderly subjects may experience more side effects after administra tion of the recommended dosage of sulfisoxa zole for young adults.…”
Section: Discussionmentioning
confidence: 99%